(-3)-4j=(-6j)+19

Simple and best practice solution for (-3)-4j=(-6j)+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3)-4j=(-6j)+19 equation:



(-3)-4j=(-6j)+19
We move all terms to the left:
(-3)-4j-((-6j)+19)=0
We add all the numbers together, and all the variables
-4j-((-6j)+19)-3=0
We calculate terms in parentheses: -((-6j)+19), so:
(-6j)+19
We get rid of parentheses
-6j+19
Back to the equation:
-(-6j+19)
We get rid of parentheses
-4j+6j-19-3=0
We add all the numbers together, and all the variables
2j-22=0
We move all terms containing j to the left, all other terms to the right
2j=22
j=22/2
j=11

See similar equations:

| 2-8v=-10-10v-6 | | -4f+2(4f-52)=19 | | -6=3n=12 | | 6x+8-3x=3x-24 | | 5(x+4)=(5*1x)+(5*4)=5x+20 | | X+90=7x | | (6x+5)=89 | | 3x²+2x-16=0 | | 7w+6=5w+9 | | -8m-8+7m=-3 | | 3v^2+63=0 | | 16=3(y+3) | | 3c+5=23* | | 2,5*(2-3x)+6,3x=3*(1,2-0,6x)+1,1 | | t-44=32 | | 27=13+y | | 7r+-20r+4=17 | | 17x-25=17(4)-25 | | 15h+20=20h+10 | | 0.5(8x-10)=4x-5 | | 4x-12=132 | | 29+3x=7 | | (8x-14)+(2x+4)=180 | | -8.8=w-(-1.1) | | 16/32=x/24 | | 14s+2=4 | | 30=5/7u | | 9h-5h+4=20 | | 3(x-4)=6(2x+3) | | 17x+8+7x+4=180 | | 180=2x+96+x+12 | | (2m-2)(4m-8)=0 |

Equations solver categories